Effects of vasodilating medications on cerebral haemodynamics in health and disease: systematic review and meta-analysis. Issue 6 (June 2019) - Webb, Alastair J.S.
Abstract : Objectives: Vasodilating antihypertensives prevent stroke and potentially cerebral small vessel disease but their effects on cerebrovascular haemodynamics beyond blood pressure lowering are unclear. Methods: We searched PubMed, Medline, Embase, Cinahl, Psychinfo, Health Business Elite and Health Management Information Consortium for randomized studies of vasodilating medications, compared to no treatment or nonvasodilators, that reported effects on cerebral blood flow (CBF), mean blood flow velocity (MFV) or cerebrovascular reactivity. Absolute and standardized mean differences (SMD) were combined by inverse-variance weighted fixed or random-effects meta-analysis stratified by study design, population characteristics and vasodilator class. Results: In 35 studies reporting 57 comparisons, there was a reduction in SBP (−4.13 mmHg, −7.55 to −0.71, P  = 0.018) but no change in MFV (ΔMFV 1.11, confidence interval −0.93 to 3.14, P  = 0.29, 23 comparisons). MFV increased in patients with underlying conditions (3.41, 0.24 to 6.57, P  = 0.04) but not in healthy study participants (−1.27, −5.18 to 2.64, P  = 0.68), with no differences by vasodilating drug class. Cerebral pulsatility index was reduced across all studies (Δ pulsatility index −0.04, −0.07 to −0.02, P  = 0.001; Δ pulsatility index -SMD −0.32, −0.47 to −0.16, P  < 0.001), except in studies reporting responses to single drug doses (Δ pulsatility index 0.00, −0.09 to −0.08, P  = 0.93). Despite evidence of reporting and publication bias, there was an apparent consistent reduction in CBF with vasodilators (CBF-SMD −0.24, −0.46 to −0.02, P  = 0.03) with a significant increase in cerebrovascular reactivity-SMD (0.48, 0.13–0.83, P  = 0.007). Conclusions: Despite reducing SBP, vasodilators did not significantly impair absolute CBF but improved cerebrovascular pulsatility and reactivity, suggesting therapeutic potential in preventing stroke and cerebral small vessel disease. Abstract : Supplemental Digital Content is available in the text